PLATINUM GROUP ELEMENTS IN KOSTOMUKSHA KOMATIITES AND BASALTS: IMPLICATIONS FOR OCEANIC CRUST RECYCLING AND CORE-MANTLE INTERACTION - Puchtel I.; Humayun M. (My University, 2000)
We report precise PGE (Os, Ir, Ru, Pt, and Pd) concentrations for komatiite-basalt lava sequences of the Kostomuksha greenstone belt, and for the komatiite standards KAL-1 (Abitibi) and WITS-1 (Barberton). The flowtop breccia komatiites (MgO = 27.5%) from the Kostomuksha sequence, which represent the composition of the primary komatiite liquid, have Os = 1.5 ± 0.1 ppb, chondritic (Os/Ir)N = 1.06 ± 0.05, and moderately fractionated PGE patterns, (Pd/Os)N = 6.5 ± 0.4. Based on the KAL-1 standard, the Alexo primary liquid had Os = 1.8 ± 0.1 ppb, (Os/Ir)N = 1.05 ± 0.05, and (Pd/Os)N = 8.5 ± 1.0. PGEs in the Kostomuksha komatiites exhibit incompatible behavior during magmatic differentiation, with bulk D values of Os, Ir = 0.75, Pt = 0.52 and Pd = 0.PGE abundances from Kostomuksha komatiites and basalts were used to calculate the Pt/Os and Re/Os composition of a magnesian Archean oceanic crust. The Pt-Re-Os isotopic evolution of this crust was modeled, indicating that coupled 186,187Os enrichments observed in some modern plumes require a non-crustal source. A previously proposed model for core-mantle interaction by physical admixture was evaluated and was shown to produce mantle sources with high PGE abundances (Os = 6 to 14 ppb, Pd = 140 ppb for 1% outer core addition) and (Os/Ir)N ≥ 1, depending on the assumptions made. These features were not observed in the Kostomuksha komatiites (γ187Os(T) = +3.6), shown here to be derived from a reservoir with ∼25% lower absolute PGE abundances than primitive mantle. If the radiogenic initial 187Os/188Os in the Kostomuksha komatiite is an outer core signature, then core-mantle interaction cannot have involved physical admixture of outer core material into mantle plume sources. Instead, it must have occurred in the form of isotopic equilibration between liquid outer core and solid mantle at the core-mantle boundary.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей